2011
DOI: 10.3892/ijo.2011.1098
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a novel antagonist of growth hormone releasing hormone on cell proliferation and on the key cell signaling pathways in nine different breast cancer cell lines

Abstract: Abstract. Growth hormone releasing hormone (GHRH) antagonists have been developed for the treatment of various cancers. We investigated the effects of a novel GHRH antagonist, MIA-602, on nine breast cancer cell lines, differing in their expression for estrogen-, progesterone-and HER-2 receptors. We detected the presence of pituitary-type GHRH receptors (pGHRH-R) on 6 of the 9 breast cancer cell lines. The main splice variant of pGHRH-R, SV1, was found on all 9 cell lines. MTT assay showed that following treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The results confirmed that GHRH antagonists significantly decreased viability in the three cell lines studied. A reduction of viability has been described in breast and prostate tumor cells with the antagonist JMR-132 [22, 23] as well as in other cell types with other GHRH antagonists [10, 2427]. Since the variations in metabolic activity provoked by GHRH antagonists may be due to mitogenic changes, we performed proliferation assays on the three cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The results confirmed that GHRH antagonists significantly decreased viability in the three cell lines studied. A reduction of viability has been described in breast and prostate tumor cells with the antagonist JMR-132 [22, 23] as well as in other cell types with other GHRH antagonists [10, 2427]. Since the variations in metabolic activity provoked by GHRH antagonists may be due to mitogenic changes, we performed proliferation assays on the three cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have detailed the effects of treatment with GHRH antagonists on the growth of breast cancers. [ 16 , 28 , 46 , 47 ] However, the role of GHRH in the regulation of inflammatory cytokine expression in triple negative breast cancer has not been fully investigated. This study illustrates the benefits of using GHRH antagonists for the treatment of cancers which are highly treatment-resistant.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 17 ] Growth hormone subsequently stimulates the release of hepatic insulin-like growth factor, which is a major anabolic growth factor and a potent mitogen for many neoplasms. [ 17 - 20 ] Biologically active GHRH, mRNA for GHRH, GHRH receptors (GHRH-R), and GHRH-R splice variants have been identified in surgical specimens and tumor cell lines of a multitude of human cancers, including various types of breast cancer [ 21 - 28 ]. GHRH acts as an autocrine/paracrine growth factor in human cancers [ 16 , 29 - 31 ] including breast [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have detailed the effects of treatment with GHRH antagonists on the growth of breast cancers. [ 6 , 20 , 57 , 58 ] The study presented herein illustrates the role of GHRH signaling in the regulation of drug resistance in TNBC. Our results also demonstrate the ability of a GHRH antagonist, MIA-602, to be a potential new treatment for drug resistant cancers.…”
Section: Discussionmentioning
confidence: 84%